Children With Cochlear Implants Use Semantic Prediction to Facilitate Spoken Word Recognition. - Blomquist, Christina; Newman, Rochelle S.; Yi Ting Huang; Edwards, Jan (Journal of Speech, Language & Hearing Research, 2021)
Purpose: Children with cochlear implants (CIs) are more likely to struggle with spoken language than their agematched peers with normal hearing (NH), and new language processing literature suggests that these challenges may be linked to delays in spoken word recognition. The purpose of this study was to investigate whether children with CIs use language knowledge via semantic prediction to facilitate recognition of upcoming words and help compensate for uncertainties in the acoustic signal. Method: Five- to 10-year-old children with CIs heard sentences with an informative verb (draws) or a neutral verb (gets) preceding a target word (picture). The target referent was presented on a screen, along with a phonologically similar competitor (pickle). Children's eye gaze was recorded to quantify efficiency of access of the target word and suppression of phonological competition. Performance was compared to both an age-matched group and vocabularymatched group of children with NH. Results: Children with CIs, like their peers with NH, demonstrated use of informative verbs to look more quickly to the target word and look less to the phonological competitor. However, children with CIs demonstrated less efficient use of semantic cues relative to their peers with NH, even when matched for vocabulary ability. Conclusions: Children with CIs use semantic prediction to facilitate spoken word recognition but do so to a lesser extent than children with NH. Children with CIs experience challenges in predictive spoken language processing above and beyond limitations from delayed vocabulary development. Children with CIs with better vocabulary ability demonstrate more efficient use of lexical-semantic cues. Clinical interventions focusing on building knowledge of words and their associations may support efficiency of spoken language processing for children with CIs.